Protrusive growth from giant liposomes driven by actin polymerization - Miyata, Hidetake (The National Academy of Sciences, 1999)
Development of protrusions in the cell is indispensable in the process of cell motility. Membrane protrusion has long been suggested to occur as a result of actin polymerization immediately beneath the cell membrane at the leading edge, but elucidation of the mechanism is insufficient because of the complexity of the cell. To study the mechanism, we prepared giant liposomes containing monomeric actin (100 or 200 μM) and introduced KCl into individual liposomes by an electroporation technique. On the electroporation, the giant liposomes deformed. Most importantly, protrusive structure grew from the liposomes containing 200 μM actin at rates (ranging from 0.3 to 0.7 μm/s) similar to those obtained in the cell. The deformation occurred in a time range (30 ∼ 100 s) similar to that of actin polymerization monitored in a cuvette (ca. 50 s). Concomitant with deformation, Brownian motion of micron-sized particles entrapped in the liposomes almost ceased. From these observations, we conclude that actin polymerization in the liposomes caused the protrusive formation.